Online Summer Camp - Basic Communication in Malay for UMP Postgraduate Students - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 29 July 2021 - Postgraduate Association (PGA) Session 2020/2021, in collaboration with Centre of Modern Languages, UMP conducted a program for international postgraduate students from all faculties including FK, UMP and a group of students from UTHM who are interested to learn Malay language during their study in the university.